Eficácia de inseticidas sobre Liriomyza sativae Blanchard (Diptera: Agromyzidae) em meloeiro - Lima, Alricélia Gomes de (2021)
Melon (Cucumis melo L.) encompasses a productive chain of economic importance for the states of Ceará and Rio Grande do Norte, but faces phytosanitary barriers such as the Leafminer Liriomyza sativae Blanchard (Diptera: Agromyzidae), a key pest of the crop. Its control is carried out with spray solutions throughout the crop cycle, but it has shown efficiency failures. Therefore, the objective of this work was to: determine the effectiveness of three insecticides isolated and in mixtures, on two populations of L. sativae, one kept in the laboratory and the other collected from melon-producing areas from Polo Jaguaribe-Assú, with applications in pre- and post-infestation; determine the mean lethal concentration (LC50) in post-infestation applications; in addition evaluate the possible interference of water quality and solution pH levels (4.0 and 6.0) in field population, in post-infestation. In the efficacy test, the influence of water and influence of the pH of the ready syrup, four insecticides were used, based on the highest concentration recommended by the manufacturers and two mixtures: Cyantraniliprole 200 SC (100 g a.i./L); Cyantraniliprole 100 OD (50 g a.i./L); Abamectin 18 EC (0.018 g a.i./L); Cyromazine 750 WP (90 g a.i./L); Cyantraniliprole 100 OD + Abamectin 18 EC (50 + 0.018 g ai/L) and Cyantraniliprole 100 OD + Abamectin 18 EC (25 + 0.018 g ai/L) and as a control, the same water used in the grouts was used in all tests. All bioassays were carried out in a completely randomized design (CRD), with each treatment consisting of 10 replications (infested plant). In the efficacy test, Abamectin, Cyromazine and the mixtures provided accumulated mortality of 97.3% for the first treatment and 100.0% for the others, considered satisfactory values in the control of L. sativae in melon, in the laboratory and field populations, in the period of post-infestation. The water from the Açú Aquifer, used by melon producers in the Vale-Assú region (Ceará and Rio Grande do Norte), has adequate characteristics for diluting the tested insecticides and mixtures, in which the Abamectin treatments caused mortality of 100.0 and 84.6 % in distilled water and water from the melon farm, respectively; and Cyromazine and the mixtures caused 100.0% mortality of L. sativae regardless of the water in which they were diluted. The pH ranges (4.0 and 6.0) did not negatively influence the effectiveness of the insecticides Cyantraniliprole, Abamectin, Cyromazine and mixtures, providing mortality above 80.0% for these treatments.